Sliver Doped Sodium Antimonate with Greatly Reduced the Band Gap for Efficiently Enhanced Photocatalytic Activities Under Visible Light (Experiment and DFT Calculation) - Chen,Chen (2021)
Abstract In this work, Ag doped NaSbO3 (ANS) was successfully synthesized and applied an efficient visible light photocatalyst. The properties of catalyst were fully characterized, and DFT (the density functional theory) computation was utilized to investigate the photocatalytic mechanism. The various characterization findings proved that Ag atoms were perfectly doped into NaSbO3 crystals, which greatly reduced the band gap, and made ANS catalyst exhibit excellent visible light absorption performance. In addition, ANS appeared great photocatalytic activities and remarkable stability. Also, electrochemical characterizations illustrated that ANS possessed stronger ability of generating and transferring electrons and holes under visible light, and the doping of Ag atoms reduced the resistance of charge transfer, thus effectively accelerated the photocatalysis reaction. Moreover, through ESR characterization and scavengers coexistent experiments, •OH and •O2- were considered to be active radicals that played a crucial role in the photodegradation process. Furthermore, DFT calculation demonstrated that ANS displayed obvious visible light excitation performance via reducing the band gap. The improvement of work function enhanced the oxidation ability of photogenerated holes, forming more hydroxyl radicals, thus boosted the photodegradation of pollutants.